Dinamika Proses Pembelajaran Pendidikan Agama Islam: Studi Komparatif Kelembagaan TK dan RA - Kurnia Urfanny (AR-RASYID : Jurnal Pendidikan Agama Islam, 2021)
The purpose of this study was to compare the learning process of Islamic religious education between Raudhatul Athfal (RA) educational institutions under the auspices of the Ministry of Religion (Kemenag) and Kindergartens (TK) under the auspices of the Ministry of Education and Culture (Kemendikbud). . This study uses a qualitative method with a descriptive approach, with the subject of teachers and students in RA. Ar-Rasyid in Sukamaju village, Sunggal sub-district and in kindergarten. The country of the builder of Sunggal, both of which are in Deli Serdang Regency, North Sumatra. Collecting data using observation, interview, and documentation techniques, with descriptive data analysis techniques. Observation objects include; (1) curriculum (determination of themes and time allocation, as well as development programs), (2) religious education materials, (3) learning process (planning, implementation and assessment). The results of this study indicate that between RA and TK educational institutions, using different curricula even though they still refer to the 2013 PAUD Curriculum, Islamic religious education materials in learning in RA are more than TK, while the learning process is generally the same, but due to the content of Islamic education materials more in RA, the learning process in RA becomes more dynamic.